Traditional Healing Methods with First Nations Women in Group Counselling - Heilbron, Carrie L.; Julius Guttman, Mary Alice (Canadian Journal of Counselling and Psychotherapy, 2007)
A traditional aboriginal healing ceremony, called the Healing Circle, was utilized in a counselling group comprised of First Nations and non-aboriginal women survivors of child sexual abuse. The traditional ceremony and aboriginal beliefs were examined for their impact on the counselling process. The ceremony and beliefs established a spiritual component which contributed positively to the group. Adhering to aboriginal culture was integral to the healing process. Suggestions for the non-aboriginal counsellor in facilitating the healing process for First Nations women are offered.